Business performance management and FDI: key differences between foreign and domestic-owned firms – a case of Slovakia - Rajnoha, Rastislav; Merková, Martina; Dobrovič, Ján; Rózsa, Zoltán (Journal of Business Economics and Management, 2018)
The empirical study defines typical investment behaviour of foreign-owned firms against local firms and highlights benefits and any discrepancies of foreign capital. The paper focuses on industrial enterprises in Slovakia mainly from the automotive, engineering and wood-processing industry (N = 164). Results show the significant dependence of foreign ownership and better business performance compared with domestic firms. The performance was expressed through ROE indicator. Enterprises with the foreign participation of property achieve better performance, most typically with ROE above 10% (p-value < 0.05). The better performance, as well as distinctive feature of intangibles and research & development investments, are typically in foreign-owned firms. Intangibles and R&D as crucial investments do not directly cause better business performance in foreign-owned firms, and we discuss the reasons. The research results offer relevant and interesting implications for managers behaviour, also public authorities as well as motives for further investigation of the business performance management and foreign direct investment issues.